A discriminating dissolution method for glimepiride polymorphs - Bonfilio, Rudy [UNESP]; Pires, Sumaia A.; Ferreira, Leonardo M. B. [UNESP]; de Almeida, Adelia E. [UNESP]; Doriguetto, Antonio C.; de Araujo, Magali B.; Salgado, Hérida Regina Nunes [UNESP] (Wiley-Blackwell, 2012)
Glimepiride, an oral antidiabetic drug, is practically insoluble in water and exists in two polymorphic forms, I and II, of which form II has higher solubility in water. Because the dissolution rate of drugs can depend on the crystal form, there is a need to develop discriminating dissolution methods that are sensitive to changes in polymorphic forms. In this work, a dissolution method for the assessment of 4 mg glimepiride tablets was developed and validated. The optimal dissolution conditions were 1000 mL of phosphate buffer (pH 6.8) containing 0.1% (w/v) of sodium dodecyl sulfate as the dissolution medium and a stirring speed of 50 rpm using a paddle apparatus. The results demonstrated that all the data meet the validation acceptance criteria. Subsequently, tablets containing forms I and II of glimepiride were prepared and subjected to dissolution testing. A significant influence of polymorphism on the dissolution properties of glimepiride tablets was observed. These results suggested that the raw material used to produce glimepiride tablets must be strictly controlled because they may produce undesirable and unpredictable effects. (C) 2011 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 101:794804, 2012
Keywords: glimepiride; dissolution rate; HPLC; microscopy; polymorphism of pharmaceuticals; X-ray diffractometry; infrared spectroscopy; differential scanning calorimetry